Dural Injury During Placement of Burrholes- Single Center Study - Biswakarma, Pushpa; Limbu, Punam (Eastern Green Neurosurgery, 2020)
Background and purpose: Dural tear is one of the unpleasant complications for the neurosurgeon during craniotomy. The injury might be outer dural injury or complete dural tear in nature. With the objective to see the frequency of dural injury and to analysis the association factor this study was performed prospectively.Material and method: This is a Prospective analytical study over the duration of 2 months. All the consecutive patients, who operated for neurosurgical pathologies where drill burr was necessary, were included in this study. Association between age, gender, diagnosis category and number of burrs and dural injury was done using Fischer’s exact test or correlation whenever necessary.Result: There were total of 19 patients enrolled in the study with mean age of patient in this study was 49.11 (S.D 17.13) years. Majority of them were male (79%) and head injury (47%) was the commonest pathology in the study. correlation between number of burr and dural tear was significantConclusion: There was no significant correlation between age and dural injury. However, significant correlation was seen between number of burr holes made during the procedure with dural injury.